Simulation of Anaerobic Digestion for Biogas Production from Food Waste Using SuperPro Designer. (2019) - Harun, N.; Othman, N.A.; Zaki, N.A.; Mat Rasul, N.A.; Samah, R.A.; Hashim, H.
Abstract: Anaerobic digestion (AD) process is a form of waste-to-energy technology commonly used to produce biogas from organic matter. The purpose of this study was to develop a simulation model of anaerobic digestion process in treating food waste to produce biogas using SuperPro Designer software. The component registration, reaction list, reactor model, and process conditions were specified in the software. The Anaerobic Digestion Model No. 1 (ADM1) was applied in this simulation. The main processes of AD, which are hydrolysis, acidogenic, acetogenic and methanogenesis, were divided into two stages. The first stage, which is hydrolysis, was modeled using a stoichiometry reactor. While the second stage, which consists of acidogenic, acetogenic, and methanogenesis, were represented by an anaerobic digester. The simulation yielded 57% of methane and 25% of carbon dioxide. Sensitivity analysis was performed to study the effect of hydraulic retention time (HRT) and food waste-to-water ratio on the methane production. The results of simulation show that an increase in HRT increased the methane composition in biogas due to longer time provided for microorganism activities to yield biogas. The results also show an increase in the methane composition when the water ratio in feed was increased because the moisture content escalated the hydrolysis and methanogenesis processes by increasing the microbes and enzymes attachment areas on the surface of the substrate. The purification of methane was performed using water scrubbing technology and the methane purity achieved was about 98.7%.